An Econometric Analysis of Changes in the Cost and Production Structure of the Trucking Industry, 1953-1982 - Daughety, Andrew F.; Nelson, Forrest D. (The Review of Economics and Statistics, 1988)
Andrew F. Daughety, Forrest D. Nelson, An Econometric Analysis of Changes in the Cost and Production Structure of the Trucking Industry, 1953-1982, The Review of Economics and Statistics, Vol. 70, No. 1 (Feb., 1988), pp. 67-75